2010
DOI: 10.5334/pb-50-3-4-277
|View full text |Cite
|
Sign up to set email alerts
|

Declarative and Procedural Working Memory: Common Principles, Common Capacity Limits?

Abstract: Working memory is often described as a system for simultaneous storage and processing. Much research -and most measures of working-memory capacity -focus on the storage component only, that is, people's ability to recall or recognize items after short retention intervals. The mechanisms of processing information are studied in a separate research tradition, concerned with the selection and control of actions in simple choice situations, dual-task constellations, or task-switching setups. both research traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 57 publications
2
76
1
3
Order By: Relevance
“…Second, trivia quiz questions could evoke reasoning strategies (e.g., rejection of implausible answers) that would require -and hence, practice -relational integration processes; that is, the coordination of information elements into structures. Recent theories consider relational integration as crucial part of WM (e.g., Oberauer, 2010;Oberauer, Süß, Wilhelm, & Wittmann, 2003), and research has shown that such processes are highly related to fluid intelligence (e.g., Oberauer, Süß, Wilhelm, & Wittmann, 2008). We can only speculate whether such processes took place during active control training, but it could serve as an explanation for the active control group also showing some improvement in the transfer tasks.…”
Section: Discussionmentioning
confidence: 87%
“…Second, trivia quiz questions could evoke reasoning strategies (e.g., rejection of implausible answers) that would require -and hence, practice -relational integration processes; that is, the coordination of information elements into structures. Recent theories consider relational integration as crucial part of WM (e.g., Oberauer, 2010;Oberauer, Süß, Wilhelm, & Wittmann, 2003), and research has shown that such processes are highly related to fluid intelligence (e.g., Oberauer, Süß, Wilhelm, & Wittmann, 2008). We can only speculate whether such processes took place during active control training, but it could serve as an explanation for the active control group also showing some improvement in the transfer tasks.…”
Section: Discussionmentioning
confidence: 87%
“…Working memory is often assumed to consist of active long-term memory on the one hand and a capacity-limited part such as the direct-access region on the other hand (e.g., Oberauer, 2009Oberauer, , 2010). Yet, as was already suggested in the Discussion of Experiment 2, our results may be better framed in a more elaborate working-memory architecture.…”
Section: Formation Of Task-sets On the Basis Of Instructionsmentioning
confidence: 99%
“…Meiran, 1996Meiran, , 2000Rogers & Monsell, 1995). When frequent task switching is imposed, two task-sets are concurrently represented in the capacity-limited portion of working memory that involves the most accessible subset of representations, to which we refer as the direct-access region (see also, Oberauer, 2009Oberauer, , 2010. Because both task-sets are simultaneously active to a certain degree and both tasks overlap, task-irrelevant responses are triggered.…”
mentioning
confidence: 99%
“…These are known as executive functions (EF), and their exact number has not been agreed on (Smith & Kosslyn, 2009). Reviews by various authors (e.g., Miyake et al, 2000;Oberauer, 2010;Nęcka et al, 2012;Cohen, Aston-Jones & Gilzenrat, 2004) demonstrate that executive function can be understood either as a control mechanism, for instance, detecting and monitoring conflicts (e.g., Cohen et al, 2004), or as processes which directly change the processing of information, such as inhibition (a consequence of response to conflict). The latter approach is adopted by Oberauer (2010), for whom EFs signify "the collection of cognitive functions or processes that serve to control the primary processes directed at solving a task" (p. 298).…”
Section: Affective-cognitive Mechanisms Of Executive Functionsmentioning
confidence: 99%
“…Short-term information storage and its simultaneous handling (attributed to purposive activity) also characterize working memory (WM) in the classical Baddeley & Hitch model (1974). However, Oberauer (2010) observed that researchers tend to focus only on one of the aspects of WM -either on the storage component, i.e., people's ability to recall or recognize items after short retention intervals (mostly in WM capacity studies), or on the information processing component ("selection and control of actions in simple choice situations, dual-task constellations, or taskswitching setups; " Oberauer, 2010, p. 277). This may be an effect of how short-term memory (STM), which is free from the procedural aspect, has traditionally been studied.…”
mentioning
confidence: 99%